Analisis Usaha Pembibitan Benih Kopi Bersertifikat Varietas Sigarar Utang di Sumatera Utara - Lubis, Susilawati; Akoeb, Erwin Nyak; Kardhinata, E. Harso; Kuswardani, Retna Astuti (Universitas Medan Area, 2020)
The development of coffee plantations carried out by the Government in the future requires a lot of coffee seeds while coffee seed entrepreneurs are very limited. One of the reasons why people/farmers are reluctant to do business in the field of coffee hatchery is the fear of experiencing losses. Therefore this research was conducted which aims to analyze the business in the field of coffee hatchery. Through the interview method, 6 (six) studies were conducted, namely CV. Wana Bhakti, KPT. Sahabat Sejati, UD. Radot, Awaluddin Sitompul, CV. Putra Perkasa and CV.Dharma Nusantara located in North Tapanuli and Pematang Siantar. The results of the business analysis showed that the entire coffee seed producers studied had very large profits as indicated by the net income of 6 coffee producers each of Rp. 429,945,000, Rp. 277,805,000, Rp. 329,845,000, Rp. 288,127,000, Rp. 272,199,000 and Rp. 719,285,000. The results of this study are expected to stimulate the community/farmers to do business in the field of certified coffee hatchery so that it can help the government in providing coffee seeds for the development of coffee plantations in North Sumatra